IMPROVING STUDENTS’ ACHIEVEMENT IN SPEAKING THROUGH THE APPLICATION OF SMALL GROUP DISCUSSION METHOD (SGD) - Azhar Aziz Lubis; Masitowarni Siregar (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
Abstract The objective of the study was to find out how effective the use of Small Group Discussion Method (SGD) in teaching speaking especially in asking and giving opinion. It was conducted as an action research which has two cycles. Each cycle has three meetings. The subject of the research was students of eleventh grade IPA-2 at SMA Negeri 1 Sei Rampah which consisted of forty-four students. The instruments of data collection were primary and secondary data. While the primary data was conducted by administering students’ speaking score in every cycle, the secondary data was conducted by the three instruments; observation sheet, questionnaire and field notes. Based on the speaking tests, students’ score improved from the first evaluation to the last evaluation. In the first test, the mean was 58,55. The second test obtained the mean 67,07 and in the last test the mean of the students was 73,50. Based on the observation sheet, questionnaire sheet and field notes, it was found that learning activity ran well. Most students felt interested in the process of learning activity and involved in their group during the discussion time. The result of the research showed that Small Group Discussion Method was able to improve students’ achievement in asking and giving opinion. Key Words: Speaking, Small Group Discussion, Improving1 Graduate status 2 Lecturer